"Wouldn't You Walk Away?" Foreclosures and Homeowner Understandings. Issue 2 (April 2019) - Cleaveland, Carol L.; Shutika, Debra Lattanzi
Social work scholarship on neoliberalism—the dominant ideology and policies shaping access to housing, jobs, healthcare, and education—is in its infancy. This study examines the ground-level impact of the subprime mortgage crisis that triggered the Great Recession in 2008, examining how homeowners interpreted the changes to their neighborhood as they witnessed a remarkably high rate of foreclosures during the economic collapse of 2008-2010. Residents of a suburban community were unaware of the lending and banking practices that transformed their neighborhoods, though these policies arguably depreciated house values and a sense of well-being. Not knowing the culpability of predatory lenders in the crisis, some residents turned to an anti-immigrant social movement to preserve their community.